(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the ethnoichthyological knowledge of fishermen in the community of Bebedouro, belonging to the district of Santo Amaro, Maranhão. Through semi-structured questionnaires it was possible to observe that fishermen only develop handmade fishing as a source of savings. Both men and women exercise the profession, and this activity begins since the childhood. In the analysis of the questionnaires, 14 species of fish were found. For most fishermen, all fish are differentiated between adult and young fish by their size. Regarding the spatial distribution of ethnospecies, fishermen differentiate the environments according to the places where they are caught and the forms used for capture, expressing this way the position that the fish occupy in the water column. Fishermen associate the breeding time with the spawning behavior. Bebedouro fishermen are unaware of the closed season, claim not to receive closed-end insurance, thus, there is no period when fishing is forbidden. The community of Bebedouro has a potential in biodiversity and fishing is essential for the community, we can characterize ethnoknowledge as an important tool, considering the lack of study and assistance for the effective development of its activities, leaving only the knowledge acquired through generations and that assist them in the fishing practice and conserving exploited resources.